Adolescent Reproductive Health Education Through Training and Counseling on Prevention of Free Relationships, LGBT and HIV AIDS at SMKN 3 Payakumbuh - Skunda Diliarosta Skunda Diliarosta (Pelita Eksakta, 2020)
The purpose of this community service is to educate students in SMKN 3 Payakumbuh How to recognize and maintain reproductive health to avoid free sex, LGBT and HIV/AIDS. The education is well packed and interesting using animated films, discussing and solving problems as well as finding joint solution through a focus group discussion (FGD). This method is done so that students can easily understand about reproductive health and can find out the consequences of free and LGBT associations and HIV/AIDS disease. For initial analysis, this activity using Kahoot application with 75 questions. This activity is done with 5 stages, which is initiated by looking at the knowledge of students, introduce the reproduction tool, Issues of LGBT and Free Sex. Recognizing HIV/AID disease and sufferer data in West Sumatera. Then conducted group discussions with problem tree methods, Focused Group discussion (FGD), discussion of plenary and briefing from the resource person related to knowledge and action of reproductive health, free sex and LGBT. This activity has change attitude of SMKN3 PAYAKUMBUH students with a determination to reject the association/sex free and LGBT through the jargon "Say No to LGBT and Free Sex", in addition to the students are able to fortify themselves from behavior, LGBT and HIV/AIDS. Because adolescent are the next generation of the nation who will fill the richness of Indonesia in the Indonesian Gold ERA in 2045, they are the hope of the nation, the sunlight that will give color to the future of the nation. It is therefore an obligation of all parties to keep them from deviant behavior.